Assessing mobile phone access, usage, and willingness among women to receive voice message-based mobile health intervention to improve antenatal care attendance in district Thatta, Sindh, Pakistan - Anam Shahil Feroz; Naureen Akber Ali; Sarah Saleem (BMC, 2020)
Abstract Background Pakistan has one of the highest maternal mortality ratios worldwide at 276/100,000 live births and only 51% percent of women receive four or more ANC visits. This means that there are missed opportunities for almost half of the women who were not able to seek the recommended antenatal visits. In Thatta district, the maternal mortality ratio is estimated at 313/100,000 live births. Various studies reported that mHealth interventions have proven to be effective to improve antenatal care and postnatal care services. However, the feasibility and effectiveness of mobile health interventions to increase uptake of preventive maternal healthcare services among pregnant women in different settings may be different due to differing patient demographics, cultural diversity, environmental and behavioral factors, availability and accessibility to mobile phones, and budgetary constraints. Prior to implementing a similar intervention in Thatta District, it is crucially important to assess the mobile phone access, usage and willingness among women to receive voice-message based mHealth intervention to improve antenatal care attendance. Methods A cross-sectional quantitative study will be used to assess mobile phone access, usage and willingness among women to receive voice-message based mHealth intervention to improve antenatal care attendance in district Thatta. The study will be conducted in Thatta district of Sindh province. Married women of reproductive age (MWRA), who are residing in selected villages of Mirpur Sakro and willing to participate will be included in the study. Multistage sampling technique will be used to recruit the 415 study participants. A structured questionnaire has been designed on Epicollect to collect data from 415 women. Data will be analyzed using IBM SPSS Statistics version 23, with a level of significance as < 0.05. Discussion This research project will provide invaluable information on the current access, usage of mobile phones among women of district Thatta and their willingness to receive voice messages to improve the antenatal care services. The study will also highlight demographic, sociocultural and economic factors associated with women willingness and readiness to receive voice messages regarding antenatal care.